Amorphization by Mechanical Milling for Making IR Transparent Glass‐Ceramics. Issue 5 (7th February 2016) - Xue, Bai; Calvez, Laurent; Allix, Mathieu; Delaizir, Gaëlle; Zhang, Xiang‐Hua
Abstract : In this article, we put forward the possibility to prepare amorphous powder from chalcogenide compositions usually located out of the glassy domain when synthesized via a conventional melt‐quenching technique. Both X‐ray diffraction and DSC techniques were used to demonstrate that the original Ge15 Ga20 S65 composition can be prepared in the amorphous state by using mechanical milling starting from raw metallic elements. Subsequent hot‐pressing by spark plasma sintering in a graphite die above the glass transition temperature leads to sintered pellets presenting a high rate of nanocrystals of about 30 nm. These as‐made glass–ceramic materials present promising transparency in the infrared range.